Factors Impacting the Export Performance of SMEs: An Exploratory Developing Country Study - Karedza, Godwell; Govender, Krishna (International Journal of Economics, Business and Management Studies, 2019)
While the ratio (29.5%) of SME exports to GDP in Zimbabwe seems to be respectable, this is very low compared to sub-Saharan countries such as Botswana (55.1%), Angola (55.8%), Swaziland (56.3%), etc. The current export performance of SMEs provides clear justification for re-thinking export the export marketing strategies of agro-based industries in Zimbabwe. Since the literature highlights that for export firms to perform better in the dynamic global environment, they need to develop ‘market-driven’ strategies, this study explores the relationship between market driven strategies and the export performance of select manufacturing SMEs in Zimbabwe. It was ascertained the two main strategies adopted by SMEs to enhance their export performance were niche focus strategy and export industrial clusters, and these are also supported by the policy-makers and export analysts. In summary, from regression and correlation analysis of the data collected from a convenience stratified sample of 332 SME owner-managers, four policy -makers and four export analysists, it was ascertained that various internal (customer focus, organizational capability and cross-functional co-operation), and external (market characteristics, industry characteristics, technology and market turbulence) factors impact the export performance of manufacturing SMEs, albeit some not significantly. SME owner-managers should therefore embed customer value, by producing products which project customer values namely, experiential, symbolic, and sacrifice value, which will positively influence the export performance of SMEs. SME owner-managers should also create vibrant teams with diverse expertise which will boost exports, and a nurture a sustainable export competitive advantage for SMEs.